Mobile Proximity Usage Behaviors Based on User Characteristics. Issue 2 (4th March 2019) - Torres, Russell; Gerhart, Natalie
ABSTRACT: Mobile adoption and use research are a relatively mature Information Systems (IS) research area; however, few studies have taken a user-centered approach to examining this phenomenon. This research focuses on the user characteristics of self-efficacy and time urgency, a construct adopted from psychology, and relates them to traditional adoption and use theories. Further, this research substitutes mobile proximity as a usage construct to explicitly recognize the features of the mobile device that make it unique, thereby enriching the use literature. The proposed model explains 24% of the variance in mobile proximity and highlights four significant hypotheses. Our findings indicate that the newly applied time urgency and mobile proximity constructs are applicable in adoption and use studies and should be further explored in IS literature. Implications for research and practice are outlined, including the relative ease of access to mobile devices and the importance of personality traits as related to adoption.